2006
DOI: 10.1073/pnas.0506811103
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state of the postperovskite phase synthesized from a natural (Mg,Fe)SiO 3 orthopyroxene

Abstract: Using the laser-heated diamond anvil cell, we investigate the stability and equation of state of the postperovskite (ppv, CaIrO3-type) phase synthesized from a natural pyroxene composition with 9 mol.% FeSiO3. Our measured pressure-volume data from 12-106 GPa for the ppv phase yield a bulk modulus of 219(5) GPa and a zero-pressure volume of 164.9(6) Å 3 when K0 ‫؍‬ 4. The bulk modulus of ppv is 575(15) GPa at a pressure of 100 GPa. The transition pressure is lowered by the presence of Fe. Our x-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
62
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 33 publications
(42 reference statements)
13
62
1
Order By: Relevance
“…In contrast, the bulk velocity, V (P, T), is smaller than that of perovskite because of their similar B S (P, T) values and the larger density () of postperovskite. Something similar is observed across the phase transition in postperovskite synthesized from natural samples of (Mg,Fe)SiO 3 orthopyroxene (14). Fig.…”
Section: Resultssupporting
confidence: 56%
“…In contrast, the bulk velocity, V (P, T), is smaller than that of perovskite because of their similar B S (P, T) values and the larger density () of postperovskite. Something similar is observed across the phase transition in postperovskite synthesized from natural samples of (Mg,Fe)SiO 3 orthopyroxene (14). Fig.…”
Section: Resultssupporting
confidence: 56%
“…This may also affect the high-P,T pPv stability, but the effects in a multicomponent system are poorly constrained (17,18,24,33). The solution mechanisms of iron under the ultrahigh-pressure condition, where the low-spin state with smaller ionic radius is predominant, are also unclear (34), although some low-pressure experiments report that iron may also influence the site preference of Al 3ϩ in Pv (35).…”
Section: Resultsmentioning
confidence: 99%
“…Iron is likely to be an important component in ppv, and its incorporation in silicate ppv has been found to have a considerable influence on the properties of the phase. Experimental studies have demonstrated that ppv can take up much more iron than silicate perovskite (pv) (14,15), and the equation of state (EOS) and phase boundaries have been determined as a function of Fe 2þ content (16)(17)(18)(19). In Al-bearing ppv, the presence of Fe 3þ may also have a significant effect on the physical properties, phase boundaries and iron partitioning (20).…”
mentioning
confidence: 99%